Diabetic Cataract in Spontaneously Diabetic Torii Fatty Rats - Kasumi Kikuchi; Miyuki Murata; Kousuke Noda; Satoru Kase; Yoshiaki Tagawa; Yasushi Kageyama; Masami Shinohara; Tomohiko Sasase; Susumu Ishida (Journal of Diabetes Research)
Spontaneously Diabetic Torii (SDT) fatty rat is a novel animal model of type 2 diabetes with obesity. SDT fatty rats develop hyperglycemia, dyslipidemia, and other diabetic complications including ocular disorders; however, diabetic cataract formation in SDT fatty rats has not been fully investigated. The aim of the current study was to investigate the characteristics of cataract in the SDT fatty rats. The mean body weight of SDT fatty rats is larger than that of age-matched Sprague-Dawley (SD) rats and control animals until 8 weeks of age, and thereafter the growing speed decreased until the end of observation at 16 weeks of age. Blood glucose levels in SDT fatty rats were significantly higher than those in SD rats throughout the observational period. Slit-lamp examination revealed that no rats showed cataract formation at 5 weeks of age; however, SDT fatty rats gradually developed cortical cataract and posterior subcapsular cataract, both of which are the common types of cataract in patients with type 2 diabetes. The levels of glucose, sorbitol, and fructose were higher in the lens tissues of SDT fatty rats in comparison with that of SD rats. Furthermore, the level of 4-hydroxynonenal (4-HNE) was higher in the lens of SDT fatty rats than in that of SD rats. By contrast, total glutathione (GSH) concentration was lower in the lens of SDT fatty rats than in that of SD rats. The present study demonstrated that the cataractogenesis in SDT fatty rats resembled human diabetic cataract formation, indicating that SDT fatty rats serve as a potential animal model in researches on human cataract associated with type 2 diabetes and obesity.